Diatrypella tectonae and Peroneutypa mackenziei spp. nov. (Diatrypaceae) from northern Thailand - Qiu Ju Shang (2018)
© 2017, German Mycological Society and Springer-Verlag Berlin Heidelberg. Two novel species of Diatrypaceae, Diatrypella tectonae and Peroneutypa mackenziei, were collected from dead wood in northern Thailand. The new species are introduced in this paper, with evidence from morphology and phylogenetic analyses. The new taxa are described, illustrated and compared with related taxa. Phylogenetic analyses of combined ITS and partial β-tubulin (β-tub) sequence data support their natural placements in the genera Diatrypella and Peroneutypa as new species.